Effect of an anxiolytic botanical containing Souroubea sympetala and Platanus occidentalis on in-vitro diazepam human cytochrome P450-mediated metabolism. (22nd November 2018) - Liu, Rui; Dobson, Corrine C; Foster, Brian C; Durst, Tony; Sanchez, Pablo; Arnason, John T; Harris, Cory S
Abstract: Objectives: A novel anxiolytic natural health product (NHP) containing Souroubea sympetala and Platanus occidentalis is available for the companion animal market and is currently being developed for clinical evaluation. Addressing the risk of potential NHP–drug interactions, this study investigated S. sympetala and P. occidentalis plant extracts, and their identified bioactive compounds, for effects on the activity of cytochrome P450 (CYP) isozymes and the metabolism of the conventional anti-anxiety medication diazepam. Methods: Souroubea sympetala and P. occidentalis extracts, a 1 : 1 blend of the two extracts, and five triterpenes were tested for inhibitory effects on human recombinant CYP3A4, CYP2D6, CYP2C9 and CYP2C19 activity using a fluorometric plate assay. Direct effects on the metabolism of diazepam were evaluated using human liver microsomes with drug and metabolite quantification by ultra-high-pressure liquid chromatography and mass spectroscopy. Key findings: The active substances betulinic acid (BA) and ursolic acid (UA) strongly inhibited CYP3A4 activity while UA and lupeol moderately inhibited CYP2C19. All extracts exhibited strong activity against the tested isozymes at 50–100 μg/ml. BA and all plant extracts blocked the formation of major diazepam metabolites. Conclusions: Betulinic acid, UA and both the extracts and blended product are expected to affect the metabolism of diazepam when given in high dose.